2015
DOI: 10.1007/s13197-014-1696-9
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of milk and cheese with microelements by dietary feed bio-preparations

Abstract: The present work reports studies on biofortification of milk and cheese with microelements. The diet of goats was supplemented with soya-based preparations with Cu(II), Fe(II), Zn(II) and Mn(II), produced by biosorption, instead of mineral salts. In innovative preparations, soya was the biological carrier of microelements. The utilitarian properties of the new preparations were tested in two groups (8 goats in each): experimental and control. The concentration of supplemented microelements was monitored in mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…The obtained preparations were used as dietary feed supplements with microelements in the zootechnical studies on fatteners and goats, with the biofortification effect being brought, thus resulting in the biofortification effect (Witkowska et al 2015).…”
Section: Pilot Plant Biosorption Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained preparations were used as dietary feed supplements with microelements in the zootechnical studies on fatteners and goats, with the biofortification effect being brought, thus resulting in the biofortification effect (Witkowska et al 2015).…”
Section: Pilot Plant Biosorption Systemmentioning
confidence: 99%
“…Our previous feeding trials on goats have shown that the use of new formulation resulted in the enrichment of milk with trace elements. The use of biological additives causes the enrichment of milk with trace elements such as copper (about 8.2 %), manganese (29.2 %) and zinc (14.6 %) (Witkowska et al 2015).…”
Section: Research Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies we showed that biomass enriched with microelement ions constituted a source of highly bioavailable minerals to animals (laying hens, pigs, goats) and can partly replace traditionally used inorganic salts as a main source of microelements [20][21][22]. In these studies it was shown that the bioavailability of microelements from the enriched biomass was higher than from inorganic salts.…”
Section: Introductionmentioning
confidence: 99%
“…Soyabased preparations with Cu(II), Fe(II), Zn(II) and Mn(II) produced by biosorption were tested also on goats. It resulted in goats' biofortified milk and cheese which could be used as designer milk to prevent micronutrient deficiencies [21]. The same enriched soybean meal was examined in the zootechnical studies on fatteners.…”
Section: Introductionmentioning
confidence: 99%